A Narrative Review of English Language Learning and Artificial Intelligence - Artha, Bhenu; Santoso, Fajar; Sari, Utami Tunjung; Bahri, Bahri; Sari, Niken Permata; Hadi, Antonius Satria; Asri, Cahya Purnama; Aditya, Ascasaputra (Allure Journal, 2026)
With the introduction of digital technology and artificial intelligence, learning English is changing dramatically.  By combining the results of the previous ten years of research, this study—which is being conducted using the narrative review method—aims to fill these gaps by offering a thorough grasp of the present trends, difficulties, and potential future directions in the use of AI to English language learning.  The majority of current research is on the effectiveness of certain AI technologies, paying little consideration to the long-term impacts on learners' sociocultural competency, language ability, and retention.  Furthermore, the majority of research to far has focused on English as a foreign language, with little attention paid to how AI can facilitate multilingualism or the acquisition of English as a second language in various sociocultural contexts. Studies examining the pedagogical, cultural, and ethical ramifications of widespread AI deployment in language instruction—particularly in non-Western contexts—are also lacking.  This study highlights both the exciting promise and the difficulties of integrating GenAI technology, providing insightful information about the changing field of AI use in English learning.  Conducting empirical research on the principles in this study is one suggestion for future research.